Localized cancer bladder : Predictive value of the G1 - check points for response to adjuvant therapy - Enas Noshy Mohamed; Abeer Bahnassy; Ahmed Selim Fouad; Alaa Meshref (Cairo : Enas Noshy Mohamed, 2010)
Muscle invasive bladder cancer is an aggressive tumor . Radical cystectomy is considered the standard treatment . However many patients experience local and distant relapse . The biological behavior cannot be adequately predicted by histological criteria alone . To evaluate the role of 6 cell cycle and apoptosis regulatory markers (cyclinD1, CDK4, bc12, bax, p16 and p14 ) as predictive and prognostic makers in muscle invasive bladder cancer and their relation to the treatment received
Thesis (Ph.D.) - Cairo University - Faculty of Medicine - Department of Radio-diagnosis
Issued also as CD
Keywords: Localized; Predictive; Response